Formulation and Characteristics Analysis of Soap with The Addition of Spirulina Platensis - H. Hadiyanto; Aniek Sri Handayani; Miftah Aqidatul Izzah; Marcelinus Christwardana (BIORE Scientia Publisher, 2023)
Cleanliness has become an integral element of daily living. Soap is often used as a cleaning agent. Soap can remove grime and microorganisms that adhere to the skin. Various types of fats or oils are often utilized as soap's primary constituents. The usage of these diverse oils alters the properties of soap, beginning with its hardness, its impact on the skin, and the resultant foam. 3 grams and 5 grams of Spirulina are added to the soap formulation. The pH test, foam height test, and organoleptic test are the test parameters. The findings demonstrated that the pH of each solid soap preparation was nine, which was in agreement with national standard criteria. The foam stability formed was 75% and 25%, and that the soap formulation maintained its color, shape, and odor for a period of ten days during storage. This research concludes that Spirulina platensis can be made into a solid soap formulation. The effects of the addition of Spirulina to solid soap include a light green color, a solid shape or solid texture, and a distinct perfume of essential tea tree oil, as well as the production of quite a bit of foam and a little coarseness.